Living Beyond the Diagnosis: The Emotional and Social Journeys of People Living with HIV/AIDS – A Scoping Review - Deviantony, Fitrio; Ashari, Muhammad; Aindani, Rafelina Putri; Ramadina, Putri Dwi (Journal of Nursing Science Update (JNSU), 2025)
Individuals living with HIV/AIDS encounter a range of psychosocial issues that significantly impact their quality of life. Among these issues, stigma and mental health are critical components in understanding the overall well-being and treatment adherence of people living with HIV/AIDS (PLWHA). The integration of mental health support into HIV care is emphasized as a vital strategy for enhancing the quality of life for this population. The study aims to explore the psychosocial challenges faced by PLWHA in Indonesia and underscores the imperative of incorporating mental health assistance into HIV care frameworks. A literature review was conducted, examining studies published between 2020 and 2024. Relevant articles were sourced from databases such as Google Scholar and PubMed, utilizing keywords including "psychosocial impact on HIV," "HIV," and "mental health." The findings indicate a significant correlation between stigma and the mental health status of PLWHA. Many individuals experience heightened levels of anxiety, depression, and social isolation, all of which impede their treatment adherence and adversely affect their overall well-being.  The review advocates for the establishment of comprehensive support systems that address both the physical and mental health needs of this demographic. In conclusion, the psychosocial challenges experienced by PLWHA are critical determinants of their health outcomes. Therefore, enhancing mental health services and mitigating stigma are essential for improving the quality of life for PLWHA. Future interventions should focus on creating supportive environments that promote resilience and overall well-being among this vulnerable population.